The Development of Teaching Materials Lecture of Fiction Based Tidayu Culture Integrated Mobile Learning - Susan Neni Triani; Eti Sunarsih (AKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
This research based on students by difficulty in understanding analysis prose in lecture study prose fiction. Learning are now more led to the topic on local wisdom. West kalimantan constituting a province that has many tribes. Three large tribe living in west kalimantan, tionghua, dayak, and melayu. This study focused on tidayu folklore. So learning lecture study prose fiction developed into the development of material lecture prose fiction based tidayu culture integrated mobile learning. Problems in this research is how vaidty, practicality and effectivity whether the use of teaching lecture study prose fiction based tidayu culture integrated mobile learning in learning the prose fiction in STKIP singkawang. The research method used in this research is a research and Development (R&D) method of development with ADDIE research approach. The research period was held from March to July 2019 at the STKIP Singkawang. The test subjects in this study were students of the Bahasa dan Sastra Indonesia study Program of semester III as many as 17 students. Results of the study showed that the teaching materials of prose fiction based Tidayu culture integrated mobile learning in the students of Pendidikan Bahasa dan Sastra Indonesia program study STKIP Singkawang is valid, practical and effective in application on the learning process. Keywords: development, prose fiction, tidayu culture, mobile learning